Differential cortical contribution of syntax and semantics: An fMRI study on two-word phrasal processing. (November 2017) - Schell, Marianne; Zaccarella, Emiliano; Friederici, Angela D.
Abstract: Linguistic expressions consist of sequences of words combined together to form phrases and sentences. The neurocognitive process handling word combination is drawing increasing attention among the neuroscientific community, given that the underlying syntactic and semantic mechanisms of such basic combinations—although essential to the generation of more complex structures—still need to be consistently determined. The current experiment was conducted to disentangle the neural networks supporting syntactic and semantic processing at the level of two-word combinations. We manipulated the combinatorial load by using words of different grammatical classes within the phrase, such that determiner-noun combinations (this ship) were used to boost neural activity in syntax-related areas, while adjective-noun combinations (blue ship) were conversely used to measure neural response in semantic-related combinations. By means of functional magnetic resonance imaging (fMRI), we found that syntax-related processing mainly activates the most ventral part of the inferior frontal gyrus (IFG), along the frontal operculum (FOP) and anterior insula (aINS). Fine-grained analysis in BA44 confirmed that the most inferior-ventral portion is highly sensitive to syntactic computations driven by function words. Semantic-related processing on the contrary, rather engages the anterior dorsal part of the left IFG and the left angular gyrus (AG) that is two regions which appear to perform different functions within the semantic network. Our findings suggest that syntactic and semantic contribution to phrasal formation can be already differentiated at a very basic level, with each of these two processes comprising non-overlapping areas on the cerebral cortex. Specifically, they confirm the role of the ventral IFG for the construction of syntactically legal linguistic constructions, and the prominence of the more anterior IFG and the AG for conceptual semantics.